Sub-Lineage Specific Phenolic Glycolipid Patterns in the Mycobacterium tuberculosis Complex Lineage 1 - Gisch, Nicolas; Utpatel, Christian; Gronbach, Lisa M.; Kohl, Thomas A.; Schombel, Ursula; Malm, Sven; Dobos, Karen M.; Hesser, Danny C.; Diel, Roland; Götsch, Udo; Gerdes, Silke; Shuaib, Yassir A.; et al. (Frontiers in Microbiology, 2022)
‘Ancestral’ Mycobacterium tuberculosis complex (MTBC) strains of Lineage 1 (L1, East African Indian) are a prominent tuberculosis (TB) cause in countries around the Indian Ocean. However, the pathobiology of L1 strains is insufficiently characterized. Here, we used whole genome sequencing (WGS) of 312 L1 strains from 43 countries to perform a characterization of the global L1 population structure and correlate this to the analysis of the synthesis of phenolic glycolipids (PGL) – known MTBC polyketide-derived virulence factors. Our results reveal the presence of eight major L1 sub-lineages, whose members have specific mutation signatures in PGL biosynthesis genes, e.g. pks15/1 or glycosyltransferases Rv2962c and/or Rv2958c. Sub-lineage specific PGL production was studied by NMR-based lipid profiling and strains with a completely abolished phenolphthiocerol dimycoserosate biosynthesis showed in average a more prominent growth in human macrophages. In conclusion, our results show a diverse population structure of L1 strains that is associated with the presence of specific PGL types. This includes the occurrence of mycoside B in one sub-lineage, representing the first description of a PGL in an M. tuberculosis lineage other than L2. Such differences may be important for the evolution of L1 strains, e.g. allowing adaption to different human populations.